Morbidity or mortality? Variations in trauma centres in the rescue of older injured patients. Issue 5 (May 2016) - Zafar, Syed Nabeel; Shah, Adil A.; Zogg, Cheryl K.; Hashmi, Zain G.; Greene, Wendy R.; Haut, Elliott R.; Cornwell, Edward E.; Haider, Adil H.
Abstract: Introduction: Prior analysis demonstrates improved survival for older trauma patients (age > 64 years) treated at trauma centres that manage a higher proportion of geriatric patients. We hypothesised that 'failure to rescue' (death after a complication during an in-hospital stay) may be responsible for part of this variation. The objective of the study was to determine if trauma centre failure to rescue rates are associated with the proportion of older trauma seen. Methods: We analysed data from high volume level 1 and 2 trauma centres participating in the National Trauma Data Bank, years 2007–2011. Centres were categorised by the proportion of older trauma patients seen. Logistic regression analyses were used to provide risk-adjusted rates for major complications (MC) and, separately, for mortality following a MC. Models were adjusted for patient demographics, comorbid conditions, mechanism and type of injury, presenting vital signs, injury severity, and multiple facility-level covariates. Risk-adjusted rates were plotted against the proportion of older trauma seen and trends determined. Results: Of the 396, 449 older patients at 293 trauma centres that met inclusion criteria, 30, 761 (8%) suffered a MC. No difference was found in the risk-adjusted incidence of MC by proportion of older trauma seen. A MC was associated with 34% of all deaths. Of those that suffered a MC, 7413 (24%) died and 76% were successfully rescued. Centres treating higher proportions of older trauma were more successful at rescuing patients after a MC occurred. Patients seen at centres that treat >50% older trauma were 33% (OR = 0.67, 95% CI 0.47–0.96) less likely to die following a MC than in centres treating a low proportion (10%) of older trauma. Conclusions: Centres more experienced at managing geriatric trauma are more successful at rescuing older patients with serious complications. Processes of care at these centres need to be further examined and used to inform appropriate interventions.